Study the satisfaction of students with the teaching of cthnogrphic history teachers in Geography Course khang khay Teacher Training Colleg 2021-2022 - PHOUTSADY, Phetsamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is to study the satisfaction of students with the teaching of teachers in the subject of history, ethnology, geography, 12+4 year 3, academic year 2021-2022, Khang Khay teacher training College. the target group used in this research is the students of geography teacher system 12+4 year 3, there are a total of 16 people, the tools used in the research are questionnaires, statistics used in data analysis such as average value, standard deviation, analysis and interpretation of the results of the research. the results of the study of the satisfaction of students in the geography teacher's line to the problem of the analysis and evaluation of the teacher in the management of the study-teaching of the ethnographic course in the teacher's line of geography. Introducing the teacher's lesson to the overall satisfaction of the students is at a very high level with a mean value equal to ( X ̅ = 4.1) and a standard deviation value equal to (SD = 0.8), the organization of the teacher's activities is at a very satisfactory level with the mean value equal to (X ̅ = 4.1) and the standard deviation value is (SD = 0.8), using the teacher's question, the satisfaction of the students is in the level of satisfaction with the mean value equal to (X ̅ = 4.1) and the standard deviation value equal to (SD = 0.8), The results of the research found that the problem of the use of teaching-learning media by teachers in the subject of history and ethnology, the overall satisfaction of students is at a high level with the mean value equal to (X ̅ = 3.6) and the standard deviation value equal to (SD = 0.8).